2019
DOI: 10.1016/j.jtumed.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis is associated with disease severity and anti-double stranded DNA antibody and interferon-gamma levels in patients with systemic lupus erythematosus

Abstract: ObjectivesTo analyse the correlation between periodontitis severity and disease activity, anti-double stranded DNA (anti-dsDNA) antibody, and interferon-gamma (IFN-γ) levels in patients with systemic lupus erythematous (SLE).MethodsWe selected 61 patients with SLE (age 18–55 years) selected from a hospital in Malang, Indonesia. Clinical examination and laboratory tests were performed to assess disease activity. The severity of SLE was measured using the Systemic Lupus Erythematosus Disease Activity Index (SLED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Clinical signs of advanced periodontitis are attachment loss, inflammation of the gingiva, and bone breakdown, which are found to be higher (88.53%) in SLE patients than control. 6,7 Periodontitis starts as gingival inflammation at the gingival margin and causes irreversible damage to the periodontium. Inflammation severity may vary among individuals based on the degree of bacterial infection, and dysregulation of host inflammatory response may substantially contribute to its extent.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs of advanced periodontitis are attachment loss, inflammation of the gingiva, and bone breakdown, which are found to be higher (88.53%) in SLE patients than control. 6,7 Periodontitis starts as gingival inflammation at the gingival margin and causes irreversible damage to the periodontium. Inflammation severity may vary among individuals based on the degree of bacterial infection, and dysregulation of host inflammatory response may substantially contribute to its extent.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found this autoantibody affects vulnerable in oral health and infection. Higher anti-ds-DNA was found before had a strong positive correlation with poor oral hygiene and periodontitis in SLE patients [6].…”
Section: Discussionmentioning
confidence: 85%
“…Higher SLE activity disease also resulting in poor oral hygiene due to immune response. Recent studies also found the activity of SLE had a strong positive correlation with infection, especially periodontitis [6,7,22,23].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations